A computational prediction for the effective drug and stem cell treatment of human airway burns. Issue 10 (26th July 2016) - Park, Seungman
Abstract: Burns in the airway from inhaling hot gases lead to one of the most common causes of death in the United States. In order to navigate tissues with large burn areas, the velocity, temperature, and heat flux distributions throughout the human airway system are computed for the inhalation of hot air using the finite-element method. From there, the depth of burned tissue is estimated for a range of exposure times. Additionally, the effectiveness of drug or stem cell delivery to the burned airway tissue is considered for a range of drug or cell sizes. Results showed that the highest temperature and lowest heat flux regions are observed near the pharynx and just upstream of the glottis. It was found that large particles such as stem cells (>20 μm) are effective for treatment of the upper airways, whereas small particles (<10 μm) such as drug nanoparticles are effective in the lower airways.